Search for a SM Higgs boson in the H → Z*Z → ℓ+ℓ−qq̅ channel in the mass range 120 - 180 GeV with the ATLAS Detector at √s = 7 TeV - Zurzolo Giovanni (EPJ Web of Conferences, 2013)
A summary of the first study is given for the decay channel H → Z*Z → ℓ+ℓ−qq̅ (ℓ = e, μ) in the Higgs boson mass range 120 - 180 GeV, using the pp collision data collected by the ATLAS experiment at √s = 7 TeV at the LHC. Data driven methods to estimate the background and new techniques to improve the mass resolution of the hadronic Z boson decay are used. Events with 0 or 1 b-jets and events with 2 b-jets are treated as separated channels. No significant excess of events above the estimated background is observed; upper limits at 95% C.L. on the Higgs production cross section are derived.